An Afrocentric muse on Sis Noe blogspot in ‘counselling’ youths on courtship, marriage and sexual matters in Sunday News - Mlauzi, Jeremiah M. (Midlands State University, 2018)
The research focuses on an Afrocentric muse on Sis Noe’s blogspot in ‘counseling’ youths on courtship, marriage and sexual matters in Sunday News. It explores how relevant is Sis Noe’s ‘counseling’ role on youths as far as the handling of courtship, marriage and sexual matters is concerned within the African cultural matrix. As such, this study is largely informed by the traditional way of counseling which is rooted in the fecund African philosophy of life in dealing with or transcending life problems. The study is basically qualitative in nature. Data gathering tools considered chief in this study included the semi-structured interviews, a focus group discussion and document analysis in acquiring the needed data from the elderly people, the academics in the field of culture, the youths and the Sunday News staff. Afrocentricity theory became imperative to inform arguments and analysis of this study. The research observed that while Sis Noe’s blogspot is playing a crucial role in ‘counseling’ various youths experiencing a number of life challenges that include courtship, marriage and sexual problems amongst others, however, some of the approaches used to handle those problems tend to be Eurocentric and in turn jeopardize the African existential philosophy.